The risk of financial crises: Is there a role for income inequality? - Kirschenmann K; Malinen T; Nyberg H (ELSEVIER SCI LTD, 2022)
Could macroeconomic factors such as income inequality be the real root cause of financial crises? We explore a broad variety of financial and macroeconomic variables and employ a general-to-specific model selection process to find the most reliable predictors of financial crises in developed countries over a period of more than 100 years. Our in-sample results indicate that income inequality has predictive power beyond loan growth and several other financial variables. Out-of-sample forecasts for individual predictors show that their predictive power tends to vary considerably over time, but income inequality has predictive power in each forecasting period. (C) 2016 Elsevier Ltd. All rights reserved.